Ortaokul Öğrencilerinin Öğrenme Stilleri ve Matematiksel Problem Çözmeye Yönelik Tutumlarının İncelenmesi. - ÖZGEN, Kemal; AY, Mehmed; KILIÇ, Zülküf; ÖZSOY, Gökhan; ALPAY, Fatma Nur (Mehmet Akif Ersoy University Journal of Education Faculty, 2017)
The purpose of this study is to investigate middle school students' learning styles and mathematical problem solving attitudes according to gender, class level, mathematics achievement scores and perception of use of mathematics in real world. In addition, the purpose of this study is to determine the effects of students learning styles on mathematical problem solving attitudes. In this research, survey model has been used which is descriptive research methods. The study group of this research consists of 725 middle school students. Students are studied 5th, 6th, 7th and 8th grades at the four different middle schools in the center of three cities. Kolb learning style scale, attitude scale towards mathematical problem solving and personal information form have been used as data collection tools. In the analysis of the obtained data, ttest, chi-square, Kruskal Wallis and regression analysis were performed. The results of the data analysis demonstrate that middle school students' dominant learning styles are diverger and accommodator. It is also found that there are significant differences between learning styles according to gender and between mathematical problem solving attitudes according to class level. In addition, it is revealed that there are significant differences between learning styles and mathematical problem solving attitudes according to mathematics achievement scores and perception of use of mathematics in real world. While students' attitudes towards mathematical problem solving become positive, it has seen rising in mathematics achievement scores. Moreover, it is found that there is a relationship between students' perceptions of use of mathematics in real world and learning styles. In the study, a low-level significant correlation is found between concrete experience, reflective observation, abstract conceptualization and active experimentation variables which are components of Kolb learning styles model and mathematical problem solving attitudes.